Do acupuncture meridians exist? Correlation with referred itch (mitempfi ndung) stimulus and referral points - Silberstein, Morry (2012)
Objective To describe the relationship between referred itch (mitempfi ndung) stimulus and referral points and acupuncture meridians, noting that the neuroanatomical mechanism of mitempfi ndung has never previously been satisfactorily explained. Methods Analysis of clinical fi ndings in the author as well as subjects in four previously described studies, comparing proportions in each of fi ve groups. Results Ninety-two per cent (range 85-94%) of mitempfi ndung point pairs (stimulus and referral) aligned to a recognised acupuncture meridian with no statistical difference (p<0.05) between the fi ve data sources. Conclusion While previous authors have speculated on an association between mitempfi ndung and acupuncture, this is the fi rst description of a relationship between stimulus and referral points and acupuncture meridians. The author suggests that the transmission of mitempfi ndung along acupuncture meridians may involve a series of C-fi bre-Merkel cell relays, with the fi nal referred itch sensation caused by substance P release triggering mast cell degranulation.